Implementing the Community Healthcare Network Model in Mid West community health care - Marie Boyle; Anne Geary (James Cook University, 2023)
Background: Integrated care, underpinned by a health and wellbeing approach, is central to Ireland's health service reform. This new Community Healthcare Network (CHN) model is in the process of implementation across Ireland as part of the Enhanced Community Care (ECC) Programme, a key deliverable of the Sláintecare Reform Programme that aims to 'shift left', ie change the way health care is delivered and bring more support closer to home. ECC aims to deliver integrated person-centred care, enhance Multidisciplinary Team (MDT) working, strengthen links with GPs and strengthen community supports. There are nine learning sites and 87 further CHNs.DeliverablesA new Operating ModelStrengthening governance and enhancing local decision-making through the development of a Community health network operating model, including a Community Healthcare Network Manager (CHNM), a GP Lead and Multidisciplinary Network Management Team.Enhancing primary care resources.Enhanced MDT workingProactive management of people with complex care needs in the community facilitated by the Multidisciplinary Team and new Clinical Coordinator (CC) and Key Worker (KW) roles.Redesign of the Clinical Team Meeting to allow virtual attendance and focused case discussion will facilitate GP attendance.Developing integrated care pathways between CHNs, Specialist Hubs (Chronic Disease and Frail Older Persons) and Acute Hospitals.Strengthening Community Supports, eg ALONE.Population Health ApproachPopulation health needs assessment utilising census data and health intelligence, local knowledge from GPs, PCTs, community services and service user engagement.Risk Stratification - resources applied intensively in a targeted manner to a defined population.Enhanced Health Promotion - addition of a Health Promotion and improvement officer to each CHN and the Healthy Communities Initiative, which aims to implement targeted initiatives to tackle challenges within specific communities, eg smoking cessation, social prescribing.Key enablers for implementationAppointment of a GP lead in all CHNs is essential to strengthen relationships and bring GP voice to health service reform.The CHN model has the potential to support the delivery of integrated care, providing opportunities for enhanced MDT working by identifying key personnel (CC, KW and GP lead) to support effective MDT functioning.Redesign of the clinical team meetings will support GP involvement and enhance collective decision making and joint working.Population risk stratification is necessary to deliver targeted services. CHNs need to be supported to carry out risk stratification. Furthermore, this is not possible without strong links with our CHN GPs and data integration.An integrated community case management system that can 'talk' to GP systems is a critical enabler for integration.Evaluation: The Centre for Effective Services completed an early implementation evaluation of the 9 learning sites. From initial findings, it was concluded that there is an appetite for change, particularly in enhanced MDT working. Key features of the model, such as the introduction of the GP lead, clinical coordinators and population profiling, were viewed positively. However, respondents perceived communication and the change management process as challenging.